Enhancing Public Understanding of ASEAN: towards Stronger Integration - Cifebrima Suyastri, Rio Sundari, Dini Tiara Sasmi (Journal of Diplomacy and International Studies, 2023)
This article examines hos ASEAN can engage and empower the public in order to increase their understanding and participation in the integration process. It seeks to promote an informed and engaged ASEAN citizenry by investigating strategies and approaches. Understanding the perspectives, concerns, and aspirations of the public is essential for devising effective communication and educational programs. Examining successful examples, best practices, and learned lessons, the essay formulates recommendations for promoting a more robust and sustainable framework of integration. The ultimate objective is to increase public understanding of ASEAN and create an informed and empowered public that actively supports and participates in the process of integration.